Is the landing error scoring system reliable and valid? A systematic review - Hanzliková, I.; Hébert-Losier, K. (Sports Health: A Multidisciplinary Approach, 2020)
Context: The Landing Error Scoring System (LESS) is a clinical tool often used in research and practice to identify athletes presenting high injury-risk biomechanical patterns during a jump-landing task.